PENERAPAN TRANSFORMASI PERPUSTAKAAN BERBASIS INKLUSI SOSIAL DI PERPUSTAKAAN UMUM (SEBUAH KAJIAN LITERATUR) - Zalmi, Fathonah Az Zahra (UIN Imam Bonjol Padang, 2024)
This research is an application of social inclusion-based library transformation in public libraries. Public libraries serve as centers of information and knowledge dissemination, and their role is increasingly important in the digital era. This research uses a qualitative method with a literature study approach to evaluate the implementation of social inclusion-based libraries in various regions and identify key supporting factors and obstacles faced. The results show that social inclusion-based libraries play an important role in improving people's knowledge and skills, as well as providing a comfortable and open space for everyone. This library transformation promotes equality, justice and sustainable development, and increases literacy and community participation in library activities. Thus, social inclusion-based libraries can contribute to the overall well-being of society.